2017
DOI: 10.3233/jad-170720
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome

Abstract: Background The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer’s disease (AD). Objective The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. Methods Twenty-four adults (13 male, 11 female; 39 ± 7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 65 publications
(84 reference statements)
2
28
0
Order By: Relevance
“…Interestingly, the DS/no dementia/PiB positive group had [C‐11]PiB retention levels exceeding threshold cutoffs in anterior cingulate, frontal cortex, and striatum, and levels at threshold cutoffs in the precuneus cortex, lateral parietal cortex, and temporal cortex. In contrast, the DS/dementia/PiB positive group had [C‐11]PiB PET levels higher than cutoff values in all regions examined despite similar mean age when compared to the DS/no dementia/PiB positive group (Lao et al, ). Another [C‐11]PiB PET study of DS/no dementia/PiB negative ( n = 41, mean age 35 years) and DS/no dementia/PiB positive ( n = 22, mean age 44 years) found that PET amyloid status did not influence between‐person differences in cognition independent of age (Hartley et al, ).…”
Section: Neuropathology Substrates Of Amyloid Pet Ligands In the Ds Bmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, the DS/no dementia/PiB positive group had [C‐11]PiB retention levels exceeding threshold cutoffs in anterior cingulate, frontal cortex, and striatum, and levels at threshold cutoffs in the precuneus cortex, lateral parietal cortex, and temporal cortex. In contrast, the DS/dementia/PiB positive group had [C‐11]PiB PET levels higher than cutoff values in all regions examined despite similar mean age when compared to the DS/no dementia/PiB positive group (Lao et al, ). Another [C‐11]PiB PET study of DS/no dementia/PiB negative ( n = 41, mean age 35 years) and DS/no dementia/PiB positive ( n = 22, mean age 44 years) found that PET amyloid status did not influence between‐person differences in cognition independent of age (Hartley et al, ).…”
Section: Neuropathology Substrates Of Amyloid Pet Ligands In the Ds Bmentioning
confidence: 91%
“…However, as discussed earlier, patterns of amyloid PET ligand retention likely do not fully recapitulate patterns described in neuropathology studies at least at initial stages of amyloid deposition in DS. In a smaller study including DS/no dementia/PiB negative ( n = 16, mean age 35 years), DS/no dementia/PiB positive ( n = 5, mean age 47 years), and DS/dementia/PiB positive subjects ( n = 3, mean age 49 years) the same group reported correlations of SUVR with age (all participants combined) in multiple neocortical areas and striatum (Lao et al, ). Correlations between [18‐F]Florbetapir PET amyloid and age were reported in a small study including DS/no dementia ( n = 10, mean age 36 years) and DS/dementia ( n = 5, mean age 50 years) subjects (Sabbagh et al, ).…”
Section: Neuropathology Substrates Of Amyloid Pet Ligands In the Ds Bmentioning
confidence: 98%
See 3 more Smart Citations